THE USE OF GRAMMAR TRANSLATION METHOD (GTM) IN TEACHING BAHASA INDONESIA TO FOREIGN LEARNER - Agustina Lestary (UMBanjarmasin, 2019)
Grammar Translation Method (GTM) has been regarded as traditional method of teaching language. Many teachers might recommend other communicative method. However, in this paper, the writer shares her experience in teaching Bahasa Indonesia to foreign learners by using GTM. The writer provides the activities that can be used in this method and describes the characteristics of the learner. After all, just like other methods, it is important for the teachers to pay attention to the characteristics of the learners before applying certain methods.